Arbuscular mycorrhizal fungi associated with some fern species collected from Kumaon region of Western Himalaya - SHAMPA BHATTACHARYYA, RAJYASRI GHOSH*, SHREYA SENGUPTA and (Indian Phytopathology, 2012)
Effect of three chemical compounds on growth and yield of blue oyster mushroom, Hypsizygus ulmarius was studied in three separate experiments on soaking of substrate, spray on growing beds and soaking followed by spray. Soaking with Ferrous sulphate (FeSO4) resulted in maximum yield of sporocarps (726.2g per kg dry substrate) followed by Magnesium sulphate (MgSO4), Potassium nitrate (KNO3) and untreated (620g) respectively. In spray treatment, maximum yield of 792.8 g per kg dry substrate was recorded in FeSO4 followed by MgSO4, KNO3 and untreated (595.0 g) respectively. Maximum yield of sporocarps (931.4 g per kg dry substrate) was recorded with T-3 (soaking in MgSO4 solution followed by spray with FeSO4) followed by T-6 (KNO3 followed by FeSO4), T-2 (MgSO4 followed by KNO3) and T-4 (KNO3 followed by MgSO4). Minimum yield of sporocarps (591.29) was recorded in T-7 by MgSO4).